The global burden of high fasting plasma glucose associated with zinc deficiency: Results of a systematic review and meta-analysis - Wirth, James P.; Zeng, Wu; Petry, Nicolai; Rohner, Fabian; Glenn, Scott; Donkor, William; Wegmuller, Rita; Boy, Erick; Lividini, Keith (2023)
Non-communicable diseases (NCDs) account for the largest share of the global disease burden, and increasing evidence shows that zinc deficiency (ZD) contributes to NCDs by inducing oxidative stress, insulin resistance, and impaired lipid metabolism. A systematic review and meta-analysis was conducted to determine whether ZD was associated with fasting plasma glucose (FPG), a key risk factor for NCDs. A random effects meta-analysis was conducted to determine the strength of the association in the form of an odds ratio (OR) and subsequently the population attributable risk (PAR) with population prevalences of high FPG. The disease burden from high FPG attributable to ZD was expressed as disability adjusted life years (DALYS). Data from seven studies were obtained as part of the systematic review. The meta-analysis shows a significant (p<0.01) inverse relationship between ZD and high FPG (OR = 2.34; 95% CI: 1.16, 4.72). Globally, the PAR of ZD’s contribution to high FPG is 6.7%, with approximately 8.2 million high FPG DALYs attributable to ZD. Cardiovascular diseases, diabetes, and chronic kidney diseases account for more than 90% of the total DALYs. Total DALYs attributable to ZD are largest in the “Southeast Asia, East Asia, and Oceania” and “High Income” Super Regions. While the disease burden is highest among populous countries (e.g., China, India, USA), the population-standardized DALYs are highest among island nations, particularly island nations in the South Pacific and Caribbean. While ZD accounts for a small share of the high FPG disease burden, the total number of DALYs far surpasses other estimates of the disease burden attributable to ZD, which focus on diarrheal diseases in childhood. Zinc interventions are urgently needed to help address the increasing disease burden from NCDs, and the double burden of malnutrition.